Assessment of Material Quality and Workmanship in Building Construction: A Case Study of Makawanpur District - K.C, Mahesh; Bist, Trilok Chandra (International Journal on Engineering Technology and Infrastructure Development, 2025)
The selection of good-quality building materials is essential in a construction project. One of the important contributing factors to the quality of concrete is the aggregate used in it. This study mainly focuses on identifying and ranking the factors that influence the quality of building construction and workmanship. A questionnaire was developed based on identified factors that were taken based on the literature to obtain opinions from engineers and sub-engineers of the local government of Makawanpur district. This study also analyzes the quality of the coarse and fine aggregates of three rivers used in under-construction public and private buildings in Kailash Rural Municipality through laboratory tests. Then, based on the survey, the identified factors were ranked. From this study the topmost ten influencing factors identified are quality of materials (RII-0.95), availability of finance (money) to the owner (RII-0.93), planning and documentation (RII-0.92), design and construction details (RII-0.92), rules and regulation of government(RII-0.92), experience of labor and contractors (RII-0.91), wages of labor (RII-0.91), management of project (RII-0.89), and management and supervision of contractor (RII Value- 0.89). From this study, it was found that poor supervision (RII-0.85) and lack of motivation in workers (RII-0.84) are the most important factors contributing poor workmanship, compared to other identified factors. Among various properties of the aggregate, only the physical and mechanical properties of coarse and fine aggregates were tested and evaluated. The result indicated that the coarse and fine aggregates of the three rivers as well as the sample of fine aggregate of under construction public and private building meet the requirements specified in Standard Specifications for Road and Bridge works - 2073 (with second amendment 2078) by Department of Roads (DoR), Nepal, except organic impurities presence in the sample of fine aggregate samples from the under construction building.